Differences in Upper-Body Peak Force and Rate of Force Development in Male Intermediate, Advanced, and Elite Sport Climbers - Vereide, Vegard; Andersen, Vidar; Hermans, Espen; Kalland, Jarle; Saeterbakken, Atle Hole; Stien, Nicolay (Frontiers in Sports and Active Living, 2022)
The aim of this study was to investigate the difference in climbing-specific strength and rate of force development (RFD) between intermediate, advanced, and elite male sport climbers. Seventy-eight male climbers were recruited and divided into groups based on the International Rock Climbing Research Association (IRCRA) numerical (1-32) grading system (intermediate (10-17) group (IG; n=28), advanced (18-23) group (AG; n=30) and elite (24-27) group (EG; n=20)). Peak force (Fpeak) and average force (Favg) were measured while performing an isometric pull-up on a 23mm thick campus rung. RFD was calculated from the onset of force to maximal peak force. The elite group performed better in all test parameters than the advanced (Fpeak: 39.7%, ES=1.40, p<0.001; Favg: 45.6%, ES=4.60, p<0.001; RFD: 74.9%, ES=1.42, p=0.001) and intermediate group (Fpeak: 95.7%, ES=2.54, p<0.001, Favg: 131.1%, ES=5.84, p<0.001, RFD: 154.4%, ES=2.21, p=0.001). Moreover, the advanced group demonstrated greater Fpeak (40.1%, ES=1.24, p<0.001), Favg (59.1%, ES=1.57, p<0.001) and RFD (45.5%, ES=1.42, p=0.046), than the intermediate group. Finally, climbing performance displayed strong correlations with Fpeak (r=0.73, p<0.001) and Favg (r=0.77, p<0.001), and a moderate correlation with RFD (r=0.64, p<0.001). In conclusion, maximal force and RFD in a climbing specific test are greater among climbers on higher performance levels. Independent of climbing level there is a moderate-to-strong association between maximal and rapid force production and climbing performance.